A controlled multi-party quantum dialogue protocol in the network. (19th July 2019) - Cao, Gang; Jiang, Min
A controlled multi-party quantum dialogue scheme in the network based on high dimensional multi-qudit entangled GHZ states is proposed. In our scheme, a semi-honest third party (TP) is introduced to assist the implementation of the scheme. Each user can be thought of as one node in the network and is connected by classical links and quantum links. In the network, multiple users can exchange their private messages with each other simultaneously under the control of TP. With the aid of secure classical channels and quantum channels, the proposed protocol can be ensured with unconditionally security. In addition, our protocol requires single-qudit measurements only which weakens the hardware requirements of network nodes. Compared with previous quantum dialogue protocols, our scheme demonstrates a large operating flexibility.